Foot Amputation in a diabetic patient who didn’t follow-up for five years - Maharjan, Reeju; Le, Khoa (Eastern Journal of Medical Sciences, 2022)
Diabetes foot ulcers (DFUs), a vascular endothelial complication, are linked to higher morbidity and mortality. DFUs are caused by a complex mix of neuropathy, peripheral arterial disease, foot deformities, and infections. Foot ulcers are a leading cause of morbidity in diabetics, and they are usually preceded by peripheral arterial disease, neuropathy, or a combination of the three, as well as other factors. We review the case of a 46 years old man who was evaluated with a small oozing wound. He did not see his doctor about his glucose level for 5 years. When he was presented with the oozing, his X-ray of the left leg and MRI of the left lower leg without contrast revealed osteomyelitis. After three days of Clindamycin administration, the patient was taken to the operating room for a left partial ray amputation as well as a left leg incision and drainage. His wound improved from scant serosanguinous drainage to peri skin dry and peeling skin underneath after continuous dressing in his post-amputation partial ray, an overall area greatly improving and healing wound. This case report summarizes the consequences of not visiting a doctor’s office if you have diabetes symptoms.